Tractive efficiency analysis for an intelligent air-cushion tracked vehicle - Mohiuddin, A. K. M.; Hossain, Altab; Rahman, Mohammed Ataur; Aminanda, Yulfian (2010)
This study presents the tractive efficiency of an intelligent air-cushion tracked vehicle (IACTV) working on swamp terrain. Based on the total power consumption and optimum load distribution for IACTV, two main issues are studied in this paper. First, a theoretical model is developed for optimizing total power consumption of the vehicle and tractive efficiency has been investigated with the effects of load distribution on the vehicle performance. Secondly, the vehicle has the ability to response for the changeable cushion pressure based on the cushion height from the ground. The system is effective to control the intelligent air–cushion system by measuring the vehicle tractive efficiency (TE), volume flow rate (Q), cushion height (CH) and cushion pressure (CP). Experiment and simulation results showed that the optimal power consumption can be obtained and maintained by using the designed fuzzy logic system (FLS) with the load distribution ratio of 0.2 and tractive efficiency of 62%. The mean relative error of actual and predicted values from the FLS model on tractive efficiency is found as 9.2%, which is less than the acceptable limit of 10%. The goodness of fit of the prediction value from FLS is found as 0.96.